Confirmatory factor analysis of the Strengths and Difficulties Questionnaire in Singaporean kindergartners. (16th October 2015) - Bull, R.; Lee, K.; Koh, I. H. C; Poon, K. K. L
Summary: Background: The Strengths and Difficulties Questionnaire (SDQ) assesses behavioural adjustment in children aged 3 to 16 years. To ascertain the appropriateness of the scale for a specific population, it is important to examine whether the distinctiveness of the scale dimensions can be verified empirically. Aims: Confirmatory factor analysis was used to test explicitly which of three models better explain our data, and whether model fit was improved by the addition of method factors. Methods: Parents of 411 Singaporean kindergartners completed the SDQ. Results: A four‐factor multi‐trait multi‐method model (Prosocial, Conduct, Hyperactivity, Internalizing and two method factors) provided the best fit to the data. There was strong evidence for convergent and discriminant validity. However, differences in configural loading pattern indicated gender‐related differences in the mapping of the SDQ items. Discussion: Differences in factor structure across countries and gender may reflect differing conceptions of the underlying dimensions, as well as differences in normative expectations. However, our findings may allow its use as a screening tool to identify Singaporean children at risk of emotional and behavioural difficulties.